Pocket computers: a new aid to nutritional support. Issue 6479 (11th May 1985) - Colley, C M; Fleck, A; Howard, J P
Abstract : A program has been written to run on a pocket computer (Sharp PC-1500) that can be used at the bedside to predict the nutritional requirements of patients with a wide range of clinical conditions. The predictions of the program showed good correlation with measured values for energy and nitrogen requirements. The program was used, with good results, in the management of over 100 patients needing nutritional support. The calculation of nutritional requirements for each patient individually facilitates more appropriate treatment and may also produce financial savings when compared with administration of a standard feeding regimen to all patients.